Significance of visuomotor behavior rehearsal in explaining athletic performance disaster - Saha, Soumendra (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
Present research was earned out to identify the integral processes of the psychological aspect of configuration of mental image of high sport performance based on the feedbacks received from the psychomotor coordinative performance of physical skill. Assessment of mood variables and projective evaluation of inner core emotionality substantiated with the autonomic indices of emotionality revealed that emotional feelings of suspicion had inhibitive impact onto changes in the feelings of irritability in the athletes. Higher extent of autonomic competence observed in athletes, was found contributed by higher self-esteem, pleasant affect and high level of emotional flexibility. Visuo-motor behavior rehearsal (VMBR) activity was observed to facilitate in the development of cognitive schema required for adequate transitions from discrete to serial motor skill development, which evidentially helped the players to display faster agile performance. Findings also suggested that, bidirectional motor learning skill and muscle steadiness were observed as significance factors for reduction in erroneous motor performance. Furthermore, faster recovery from autonomic stress was identified as essential for psychobiological adaptation required for modification in erroneous motor performance. Finally, dexterity and optimal muscle contraction along with efficient motor learning skill are required to adopt an optimal level of VMBR training required for heightened soccer performance.